1997
DOI: 10.1002/(sici)1096-9861(19970721)384:1<71::aid-cne5>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Differential central projections of physiologically characterized horizontal semicircular canal vestibular nerve afferents in the toadfish,Opsanus tau

Abstract: Anatomical and neurophysiological studies were undertaken to examine the central projection pattern of physiologically characterized horizontal semicircular canal vestibular nerve afferents in the toadfish, Opsanus tau. The variations in individual response characteristics of vestibular nerve afferents to rotational stimulus provided a means of typing the afferents into descriptive classes; the afferents fell into a broad continuum across the spectrum from low-gain, velocity-sensitive to high-gain, acceleratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The ventral vestibular division of the DON (Highstein et al, 1992;Mensinger et al, 1997) also contributes homotopic projections to the commissural tract, leading to speculation that the commissural tract may be part of a common mode rejection circuit, as has been described in the electrosensory medulla of skates (New and Bodznick, 1990;Bodznick et al, 1999). Rejection of redundant bilateral information (or self-generated noise from opercular movements) may be a component of the DON commissural tract, but comparison of left and right auditory inputs by toadfish has an obvious role in directional hearing as well (Fay, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The ventral vestibular division of the DON (Highstein et al, 1992;Mensinger et al, 1997) also contributes homotopic projections to the commissural tract, leading to speculation that the commissural tract may be part of a common mode rejection circuit, as has been described in the electrosensory medulla of skates (New and Bodznick, 1990;Bodznick et al, 1999). Rejection of redundant bilateral information (or self-generated noise from opercular movements) may be a component of the DON commissural tract, but comparison of left and right auditory inputs by toadfish has an obvious role in directional hearing as well (Fay, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The proximal innervation of neurons with the largest cell bodies is derived almost exclusively from irregular fibers (cf. A similar analysis has been done in the toadfish (Mensinger et al 1997). The authors classified horizontal-canal afferents by their gains and phases.…”
Section: Central Mechanisms Central Terminations Of Vestibular-nerve mentioning
confidence: 99%
“…The axons of primary auditory afferents innervating the saccule branch centrally to provide inputs to multiple sites along the rostro-caudal extent of the ipsilateral descending octaval nucleus (DON) (Edds-Walton et al, 1999). Although not clearly delineated anatomically, functional subdivisions have been demonstrated in the DON of toadfish: auditory processing occurs in the dorsal portion of the nucleus (Edds-Walton et al, 1999; Edds-Walton and Fay, 2008), whereas vestibular processing occurs more ventrally (Highstein et al, 1992; Mensinger et al, 1997). Moreover, tract-tracing studies combined with physiological recordings in the auditory midbrain have confirmed that a subset of cells in the ipsilateral and contralateral dorsal DON of the toadfish project to the auditory midbrain (torus semicircularis, TS)(Edds-Walton and Fay, 2003), along with ipsilateral and contralateral projections from secondary octaval populations.…”
Section: Introductionmentioning
confidence: 99%